Take-home and digital Lenten filter ashes for Ash Wednesday: creative ritual practices of faith during COVID-19 pandemic - Deguma, Jabin J (J Public Health (Oxf), 2021)
Before the coronavirus disease 2019 (COVID-19) pandemic, previous research cautioned that complex and meaningful quotidian rituals involving intimate touch need re-evaluation as these pose a hygienic concern in pandemic culture. Faith-based practices entail human-to-human contact that could inevitably cause the virus infection contagion if not appropriately addressed. In a World Health Organization document, the crucial role of inter-faith collaboration and sharing of best practices to combat the spread of the virus are encouraged. In this correspondence, we assert that taking home ashes and launching digital Lenten ashes filter are non-traditional yet creative ways for the Catholic Church to perform the ritual practice in celebrating Ash Wednesday. We argued that such creative ritual practices changed the landscape of faith-based practices and implied trans-local participation of the Catholic community as witnesses of faith while upkeeping public health.